Influence of digital transformation on employee innovative behavior: roles of challenging appraisal, organizational culture support, and transformational leadership style - Bindel Sibassaha, Jesna Lafortune; Pea-Assounga, Jean Baptiste Bernard; Bambi, Prince Dorian Rivel (Frontiers in Psychology, 2025)
IntroductionThis study investigates the relationships between digital transformation (DT), challenging appraisal (CA), organizational culture support (OCS), transformational leadership style (TLS), and employee innovative behavior (EINB) in Brazzaville’s banking sector. Grounded in Social Cognitive Theory and Self-Determination Theory, the research aims to provide insights into how these factors interact to influence innovation within organizations undergoing digital change.MethodsData were collected from 280 employees working in the top five banks in Brazzaville. Structural Equation Modeling (SEM) was applied using SPSS 26 and SmartPLS to analyze the relationships among DT, CA, OCS, TLS, and EINB.ResultsThe findings reveal significant positive relationships between DT and CA, DT and EINB, and CA and EINB. Moreover, CA and OCS partially mediate the relationship between DT and EINB. While CA has a significant effect on EINB, TLS moderates the DT-EINB relationship by weakening its positive impact. Hypotheses regarding these relationships were largely confirmed, except for the interaction effect of DT and TLS on EINB.DiscussionThese results highlight the crucial role of CA and OCS in facilitating the impact of digital transformation on employee innovation. Additionally, they suggest that higher levels of transformational leadership may not always strengthen innovation in digitally transforming organizations. The study provides valuable managerial implications for fostering an innovative workforce in the banking sector.